2015
DOI: 10.1371/journal.pntd.0003601
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Leishmania braziliensis Triggers Neutrophil Activation and Apoptosis

Abstract: BackgroundNeutrophils are the first line of defense against invading pathogens and are rapidly recruited to the sites of Leishmania inoculation. During Leishmania braziliensis infection, depletion of inflammatory cells significantly increases the parasite load whereas co-inoculation of neutrophils plus L. braziliensis had an opposite effect. Moreover, the co-culture of infected macrophages and neutrophils also induced parasite killing leading us to ask how neutrophils alone respond to an L. braziliensis exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
3
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 63 publications
(82 reference statements)
2
32
3
4
Order By: Relevance
“…Despite observations of murine neutrophils to the contrary [21,23], our data also showed activation of “bystander” human PMNs in cultures containing L. infantum infected neutrophils. Bystander activation was not observed when fresh PMNs were incubated in conditioned medium from either L. infantum or L. infantum infected neutrophils.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Despite observations of murine neutrophils to the contrary [21,23], our data also showed activation of “bystander” human PMNs in cultures containing L. infantum infected neutrophils. Bystander activation was not observed when fresh PMNs were incubated in conditioned medium from either L. infantum or L. infantum infected neutrophils.…”
Section: Discussioncontrasting
confidence: 99%
“…They are the first cell to migrate to, and take up parasites at the site of in vivo infection with either L. major [5,18–20] or with L. infantum [6] species. Indeed, there appears to be distinct differences in the way various species of Leishmania result in activation and otherwise affect neutrophils [10,2123]. In the context of disease progression, it has been suggested that, rather than control the infection, neutrophils exacerbate disease onset either by delaying apoptosis, by impairing activation of dendritic cells, or by serving as a vehicle route for silent entry of the parasite [4,2426].…”
Section: Introductionmentioning
confidence: 99%
“…The phagocyted microbes are destroyed by oxidative and nonoxidative mechanisms inside the neutrophils cytoplasm. The uptake of microbes induces the oxidative burst, increases reactive oxygen species (ROS) production and this leads to parasites clearance . Monocytes produce ROS after exposure to L. (V.) braziliensis, and in this cell, ROS contribute to control parasite multiplication .…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of microbes induces the oxidative burst, increases reactive oxygen species (ROS) production and this leads to parasites clearance. 27,28 Monocytes produce ROS after exposure to L. (V.) braziliensis, and in this cell, ROS contribute to control parasite multiplication. 29,30 In contrast to monocytes, the ROS generated by infected neutrophils prevents parasite multiplication but did not decrease the number of intracellular amastigotes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, IL-1β has been shown to have variable roles in leishmaniasis, dependent upon the infective species [6163]; notably, IL-1β was found to ameliorate L. (V.) braziliensis infection [63] but have an opposing effect for L. major , where MDSCs have been shown to exacerbate disease [62]. Further, the roles of PMNs in cutaneous leishmaniasis also appear to be variable and dependent on infecting species [61, 64, 65]; PMNs have been shown to enhance L. major infection and suppress L. (V.) braziliensis infection. It should be noted, however, that in these studies MDSCs and PMNs were not distinguished.…”
Section: Discussionmentioning
confidence: 99%